Child Religious Protection for the Muallaf Family in Sibolangit District, Deli Serdang Regency (Analysis of Child Protection Law No.35 of 2014 and the Concept of Hadhonah) - Ahmad Perdana Kusuma (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2021)
This study describes the protection of children's religion for convertible families in the sibolangit sub-district, deli serdang district. Where the children of the Muallaf family must be protected and taught about religion, where they can know what is haram and what is lawful. This type of research in writing this thesis is empirical juridical research. With field and library data collection techniques. The data collection tools are documentation study, interview and observation. Then the data is processed and analyzed descriptively. The research results obtained are; first, parents of converted familiesmust provide a strong religious basis for children in their childhood so that children can grow up to be pious children and can be useful for their religion and can also be able to spread Islam in minority places. Second, when the children are still in their age, parents must guide and supervise their children so that they can grow well in their religion. Third, the efforts of converting parents to improve Islamic religious education in children are by providing motivation, participating in children's time management, and providing facilities related to children's education. In addition, the way for converting parents to apply Islamic religious education to children is the lecture method, the exemplary method, the storytelling method.